Household chaos, emotion regulation and social adjustment in preschool children - Zimo Cai; Qian Meng (Scientific Reports)
Abstract Social adjustment is critical to preschool children’s overall development and well-being. Household chaos and emotion regulation are important influencing factors that affect young children’s social adjustment. Our study examines the interplay between household chaos and social adjustment among preschool children and investigates the mediating function of emotion regulation. Three parent report scales with sufficient reliability and validity were completed by parents from six kindergartens: the Confusion, Hubbub and Order Scale (CHAOS), Emotion Regulation Checklist (ERC), and Social Competence and Behavior Evaluation (SCBE-30). The results showed that household chaos can directly and indirectly predict social adjustment via the intermediary effect of emotion regulation. Understanding and addressing household chaos, as well as supporting children in developing emotion regulation skills, can play a significant role in promoting social adjustment and mental health in preschool children.